Seismic Performance Evaluation of An Interior Reinforced Concrete Beam-Column Joint Subjected to Cyclic Loading - Chandra, Jimmy; Wibowo, Hartanto; Christian, Yonathan Billy; Handoko, Johanna; Gunawan, Angeline; Ardenlie, Felix Go (Civil Engineering Dimension, 2025)
Many reinforced concrete (RC) buildings in Indonesia suffered severe earthquake damages due to brittle failure and poor detailing works of the beam-column joints. This experimental study aims to investigate the seismic performance of an interior beam-column joint designed according to ACI 318-19 code provisions. The specimen was subjected to static axial loading to simulate gravity loading on column and lateral quasi-static cyclic loading to simulate earthquake loading. From the experimental results, it shows that the RC beam-column joint exhibited ductile beam flexural failure as expected. However, there was a considerable bond-slip noticed on beam’s longitudinal reinforcement. In addition to the experimental study, a finite element analysis was also performed using VecTor2 software. The analysis results show that the model could simulate well the hysteretic behavior of the specimen. Furthermore, from the analysis, bond-slip was also found to be a key factor affecting the hysteretic behavior of the joint.